Financial Literacy And Individual Financial Decision Among Millennials In Indonesia After Covid-19 - Vinsensius Willson Limantoro; Sylviana Maya Damayanti (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2023)
At the end of 2019, the world was hit by the COVID-19 which caused restrictions on the activities of the world citizens. As a result of this pandemic, many people have lost their jobs and developments in technology (including fin-tech) are accelerating. Because many people have lost their jobs and find difficult to get income to survive, many people are using technology to find income. However, due to a lack of understanding of the technology used, many have been exposed to fraud or loss. This research was conducted to assess the financial literacy of millennials in Indonesia and its influence on individual financial decision, what factors affect the level of financial literacy, and how to increase the level of financial literacy of millennials. This research was conducted by processing data using Microsoft Excel and regression using SPSS from 403 respondents regarding 5 demographic questions (gender, age, occupation, last education, monthly income), 10 questions regarding financial literacy (budget planning, consumption, saving, investment, risk management), and 16 questions regarding individual financial decisions (consumption, saving, investment). The results of this research are: (1) there is a significant positive effect between the level of financial literacy and individual financial decisions. (2) there is a significant negative effect between gender and the level of financial literacy. (3) there is a significant positive effect between age, last education, and monthly income on the level of financial literacy. (4) there is no influence between occupation and level of financial literacy.